High-pressure balloon dilatation of primary obstructive megaureter in children: a systematic review - Ripatti Liisi; Viljamaa Hanna-Reeta; Suihko Anna; Pakkasjärvi Niklas (BMC, 2025)
Objective: We aimed to evaluate the effectiveness and complication rates of endoscopic high-pressure balloon dilatation (HPBD) in treating primary obstructive megaureter (POM) in children based on current literature. Specifically, we wanted to clarify the evidence on the use of HPBD in children under one year of age.
Methods: A systematic search of the literature was performed via several databases. The preferred reporting items for systematic reviews and meta-analyses guidelines were followed. The primary outcomes studied in this systematic review were the effectiveness of HBPD in relieving obstruction and reducing hydroureteronephrosis in children. The secondary outcome was to study the complication rate of endoscopic high-pressure balloon dilatation. Studies that reported one or both of these outcomes (n = 13) were considered eligible for inclusion in this review.
Results: HPBD significantly decreased both ureteral diameter (15.8 mm [range 2-30] to 8.0 mm [0-30], p = 0.00009) and anteroposterior diameter of renal pelvis (16.7 mm [0-46] to 9.7 mm [0-36], p = 0.00107). The success rate was 71% after one HPBD and 79% after two HPBD. The median follow-up time was 3.6 years (interquartile range 2.26.4 years). A complication rate of 33% was observed, but no Clavien-Dindo grade IV-V complications were reported. Postoperative infections and VUR were detected in 12% and 7.8% of cases, respectively. For children under one year of age, outcomes of HPBD seem to be similar to those in older children.
Conclusions: This study indicates that HPBD appears to be safe and can be used as the first-line treatment for symptomatic POM. Further comparative studies are needed addressing the effect of treatment in infants, and also longterm outcomes of the treatment. Due to the nature of POM, identifying those patients who will benefit from HPBD remains challenging.